Diagnostic utility of invasive EEG for epilepsy surgery: Indications, modalities, and techniques. (28th September 2016) - Jayakar, Prasanna; Gotman, Jean; Harvey, A. Simon; Palmini, André; Tassi, Laura; Schomer, Donald; Dubeau, Francois; Bartolomei, Fabrice; Yu, Alice; Kršek, Pavel; Velis, Demetrios; Kahane, Philippe
Summary: Many patients with medically refractory epilepsy now undergo successful surgery based on noninvasive diagnostic information, but intracranial electroencephalography (IEEG) continues to be used as increasingly complex cases are considered surgical candidates. The indications for IEEG and the modalities employed vary across epilepsy surgical centers; each modality has its advantages and limitations. IEEG can be performed in the same intraoperative setting, that is, intraoperative electrocorticography, or through an independent implantation procedure with chronic extraoperative recordings; the latter are not only resource intensive but also carry risk. A lack of understanding of IEEG limitations predisposes to data misinterpretation that can lead to denying surgery when indicated or, worse yet, incorrect resection with adverse outcomes. Given the lack of class 1 or 2 evidence on IEEG, a consensus‐based expert recommendation on the diagnostic utility of IEEG is presented, with emphasis on the application of various modalities in specific substrates or locations, taking into account their relative efficacy, safety, ease, and incremental cost‐benefit. These recommendations aim to curtail outlying indications that risk the over‐ or underutilization of IEEG, while retaining substantial flexibility in keeping with most standard practices at epilepsy centers and addressing some of the needs of resource‐poor regions around the world.